2004
DOI: 10.1103/physrevb.69.245113
|View full text |Cite
|
Sign up to set email alerts
|

Many-body method for infinite nonperiodic systems

Abstract: A method to implement the many-body Green function formalism in the GW approximation for infinite nonperiodic systems is presented. It is suitable to treat systems of known "asymptotic" properties which enter as boundary conditions, while the effects of the lower symmetry are restricted to regions of finite volume. For example, it can be applied to surfaces or localized impurities. We illustrate the method with a study of the surface of semi-infinite jellium. We report the dielectric function, the effective po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…As follows from this figure, there is observed a qualitative agreement between the results of our calculations and the results of the work [6]. However, the effective potential in the work [6] decreases faster to zero and there is no oscillation. In our opinion, the collective effects being insufficiently taken into account are responsible for this situation.…”
Section: Calculation Of the Effective Potential Of Electron-electron supporting
confidence: 86%
See 4 more Smart Citations
“…As follows from this figure, there is observed a qualitative agreement between the results of our calculations and the results of the work [6]. However, the effective potential in the work [6] decreases faster to zero and there is no oscillation. In our opinion, the collective effects being insufficiently taken into account are responsible for this situation.…”
Section: Calculation Of the Effective Potential Of Electron-electron supporting
confidence: 86%
“…It is shown that numerical results for g [6] correspond to the mirror electron scattering approximation for g (25).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations